Design of odd nth‐order elliptic high‐pass filters employing OTRAs. Issue 2 (30th January 2019) - Chang, Chun‐Ming; Tu, Shu‐Hui; Swamy, M.N.S.; Soliman, Ahmed M.
Abstract : Two new analytical synthesis methods are proposed for synthesising an n th odd‐order elliptic high‐pass (HP) filter using operational trans‐resistance amplifiers (OTRAs). The analytical synthesis scheme is based on the assumption of infinite trans‐resistance R m for the OTRA. The H‐spice simulations of the realised elliptic third‐order HP filters show that the realisation using less number of OTRAs has a performance better than that which uses more number of OTRAs, as is to be expected in view of the assumption that R m is infinite, when in fact it is finite in practice. However, it is shown that by slightly adjusting a single resistor, the amplitude–frequency response can be made close to the theoretical response.